Avoiding Culturalism in Technological Development: Revisiting Artificial Intelligence - Murphy, John W.; Largacha-Martínez, Carlos (Filozofia Nauki, 2023)
AI-developers face a challenge when seeking to use models that aim to be culturally sensitive. While we agree that culture is an emergent reality, there is always the risk of creating algorithms that treat culture as objective to account for various facets of the social realm. As a result, culture becomes prepackaged and autonomous. Nonetheless, culture is not only emergent but dialogically and socially invented. In this article, the point is to advance the discussion about culture by addressing a crucial philosophical issue and proposing some practical themes on how to avoid culturalism in AI development.